A Randomized Controlled Trial Comparing Traditional Plaster Cast Rehabilitation With Functional Walking Boot Rehabilitation for Acute Achilles Tendon Ruptures. Issue 11 (September 2020) - Maempel, Julian F.; Clement, Nick D.; Duckworth, Andrew D.; Keenan, Oisin J.F.; White, Tim O.; Biant, Leela C.
Background: There has been a shift toward functional nonoperative rehabilitation in the treatment of Achilles tendon rupture (ATR) despite a shortage of studies directly comparing nonoperative functional rehabilitation with traditional nonoperative immobilization. Purpose: To compare patient-reported outcome measures and functional outcomes for nonoperatively treated ATR with traditional cast immobilization or functional rehabilitation in a walking boot. Study Design: Randomized controlled clinical trial; Level of evidence, 2. Methods: In a single-center nonblinded study, 140 patients were randomized to compare treatment for acute ATR in (1) an immobilizing cast in reducing degrees of equinus over a 10-week period with 8 weeks of nonweightbearing mobilization or (2) a walking boot for 8 weeks with reducing equinus and immediate full weightbearing. Exclusion criteria were delayed presentation >2 weeks after injury, tendon reruptures, and latex allergy. Analysis was undertaken on an intention-to-treat basis. Results: A total of 69 patients (median age, 41 years [interquartile range, 33-50.5 years]) were randomized to walking boot treatment and 71 patients (41 [32-49]) to cast treatment. At 6 months, patients treated in a walking boot reported better Short Musculoskeletal Function Assessment (SMFA) dysfunction index (6.62 [2.21-12.50] vs 10.66 [4.96-13.42]; P = .050), SMFA bother index (7.29 [2.08-14.58] vs 10.42 [5.73-19.27]; P = .04), Achilles Tendon Total Rupture Score (71.5 [53.50-84.25] vs 54.0 [37-76]; P = .01), and Foot and Ankle Questionnaire core score (91 [81.89-97.55] vs 85 [78.25-92.09]; P = .04). At 1 year, there was no difference in SMFA dysfunction index (2.21 [0.74-5.88] vs 2.94 [1.47-6.62]; P = .25), SMFA bother index (2.08 [0-9.38] vs 5.21 [0.52-11.98]; P = .25), Achilles Tendon Total Rupture Score (92 [72.50-96] vs 87.5 [66.0-94.75]; P = .21), or Foot and Ankle Questionnaire core score (97.75 [89.46-99.00] vs 95.50 [90.88-97.50]; P = .18). Rerupture occurred in 5 and 11 patients ( P = .075) and venous thromboembolism in 2 and 3 patients ( P = .67) in the boot and cast groups, respectively. Fifteen patients in the boot group but none in the cast group had skin problems ( P < .001). Patients treated in a boot returned to driving at a median 12 weeks (vs 13 weeks for cast; P = .045), but there was no difference in time to return to work ( P = .48). Conclusion: Functional rehabilitation with early weightbearing is a safe alternative to traditional immobilizing treatment for ATR, giving better early functional outcomes, albeit with a higher incidence of transient minor skin complications. Registration: NCT02598843 (ClinicalTrials.gov identifier).